Metal organic polyhedron-based polymer electrolyte as well as preparation method and application thereof

By using metal-organic polyhedral-based polymer electrolytes in lithium-ion batteries, a three-dimensional lithium ion transmission path is constructed, and the problems of uneven deposition and thermodynamic instability of lithium ions caused by liquid organic electrolytes are solved, and an efficient and safe solid-state lithium battery is achieved.

CN119518084APending Publication Date: 2025-02-25JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411720524.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, liquid organic electrolytes lead to uneven deposition of lithium ions, uncontrollable dendritic growth, reduced Coulomb efficiency, shortened cycle life, and thermodynamic instability and flammability, increasing safety risks.

Method used

Metal-organic polyhedral-based polymer electrolyte is used to construct a three-dimensionally connected lithium ion transmission path through a coordination crosslinking network to form a supercrosslinked metal organic polyhedral coordinated polymer solid electrolyte, avoiding the existence of liquid and enhancing the thermal stability and interface stability of the electrolyte.

Benefits of technology

It achieves high ion conductivity, good lithium ion mobility and long-term interface stability, significantly improves the cycle life of solid-state lithium batteries, avoids battery short-circuit failure, and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518084A_ABST
    Figure CN119518084A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer electrolyte, and discloses metal organic polyhedron-based polymer electrolyte as well as a preparation method and application thereof. The metal organic polyhedron-based polymer electrolyte is obtained by compounding a metal organic polyhedron, a cross-linked polymer containing a plurality of oxygen-containing functional groups, an organic solvent and a lithium salt to obtain a precursor solution of the coordination-driven cross-linked polymer electrolyte and further carrying out a cross-linking polymerization reaction. According to the novel coordination-driven cross-linked polymer electrolyte provided by the invention, a metal organic polyhedron is used as a coordination center, so that the stability and the ion conduction performance of the electrolyte are remarkably improved, and the novel coordination-driven cross-linked polymer electrolyte does not contain any liquid, belongs to an all-solid-state electrolyte and has an obvious inhibition effect on lithium dendrites in a battery operation process; battery short-circuit failure can be avoided, and the cycle life of the solid-state lithium battery is remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer electrolytes, and in particular to a metal organic polyhedron-based polymer electrolyte and a preparation method and application thereof. Background Art

[0002] Due to the limited energy density of traditional lithium-ion batteries, it is difficult to meet the growing energy demand in emerging fields. Lithium metal anode has the highest theoretical specific capacity (3860 mAh g −1 ) and the lowest redox potential (3.04 V vs. standard hydrogen potential). However, the practical application of rechargeable lithium anodes based on traditional liquid organic electrolytes faces many obstacles: the uneven deposition of lithium ions in liquid organic electrolytes leads to uncontrollable dendrite growth, which leads to a significant decrease in Coulombic efficiency, shortened cycle life, and even short circuit. In addition, the thermodynamically unstable and flammable liquid organic electrolytes further increase the safety risks of lithium metal batteries. Compared with liquid organic electrolytes, polymer electrolytes are considered to be ideal for combination with lithium metal anodes due to their good plasticity and good adhesion to electrodes. However, the thermal stability of polymer electrolytes and the interfacial stability between electrolytes and electrodes still need to be further improved. Therefore, it is urgent to develop a new class of polymer electrolytes that can provide high ionic conductivity, good lithium ion mobility, and long-term interfacial stability.

[0003] Coordination-driven cross-linked networks are novel systems with reversible and dynamic properties, showing unique advantages in applications such as separation, catalysis, sensing, biomedicine, and optoelectronic devices. Polymer materials containing coordination bonds can overcome the contradiction between mechanical strength and dynamic self-healing. Metal-organic polyhedra, as a novel class of molecular containers / reaction bottles, are self-assembled by coordination-driven self-assembly of metal ions and organic ligands, and have potential application prospects in separation, catalysis, energy storage, biomedicine, and other fields. In particular, some metal-organic polyhedra have unique solubility, the so-called solution processability. Therefore, metal-organic polyhedra can be used as macromolecular monomers in solution and assembled with other reactants (including organic small molecules, metal ions, and macromolecules) to construct polymer networks. Compared with traditional coordination cross-linkers (such as metal ions), metal-organic polyhedra can give polymers completely new functions. Therefore, it is expected to develop new solid electrolytes with high ionic conductivity, high stability, and long-term interface stability based on metal-organic polyhedra to construct coordination cross-linked polymers.

[0004] There are some challenges that need to be overcome in practical applications of polymer solid electrolytes: (1) The room temperature ionic conductivity of polymer solid electrolytes is usually 2-3 orders of magnitude lower than that of liquid electrolytes, so most of the reported polymer electrolytes work at 60°C; (2) Due to the limited mechanical strength of polymer electrolytes and the traditional casting preparation route, the thickness of polymer solid electrolytes is in the range of 50-1000 μm, which is much thicker than commercial separators (10-30 μm). The thickness not only reduces the energy density of the battery, but also increases the transmission distance of lithium ions, which puts strict requirements on the conductivity of the electrolyte; (3) Although the plasticity of solid polymer electrolytes makes the construction of electrode / electrolyte interface relatively easier than that of inorganic solid electrolyte systems, the traditional winding battery assembly route cannot ensure the overall contact of different parts of the battery, resulting in the internal resistance of the battery being much higher than that of liquid electrolyte batteries. In addition, most reported polyethylene oxide-based solid polymer electrolytes are still flammable, resulting in poor safety. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a metal organic polyhedron based polymer electrolyte and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a metal organic polyhedron based polymer electrolyte comprises the following steps: Step 1: Dissolve dimethyl 5-hydroxyisophthalate and potassium carbonate in acetone solution and stir thoroughly; Step 2: Add 1-bromobutane to the acetone solution, stir thoroughly, and then add to the reaction solution obtained in step 1 to react thoroughly; Step 3: evaporating the reaction solvent in the solution obtained in step 2, and mixing the residue with ultrapure water, followed by extraction with dichloromethane to obtain a combined organic phase; Step 4: Dry the combined organic phase obtained in step 3 with sodium sulfate and evaporate to obtain a white solid, and recrystallize the obtained white solid from methanol to obtain the product 5-butoxydimethylisophthalate; Step 5: dissolving dimethyl 5-butoxyisophthalate in a mixture A of tetrahydrofuran and methanol, and adding a sodium hydroxide solution to the mixture A to obtain a reaction mixture; Step 6: stirring the reaction mixture obtained in step 5 under reflux, cooling to room temperature, and removing the organic solvent under vacuum to obtain a water-containing residue; Step 7: adding a hydrochloric acid solution to the aqueous residue obtained in step 6 until the pH of the solution reaches 5 to obtain a mixture B containing a white solid, then centrifuging the mixture B and removing the supernatant to obtain a precipitate, washing the precipitate with water and vacuum drying to obtain a ligand of a metal organic polyhedron; Step 8: Dissolving the obtained metal organic polyhedron ligand and copper acetate in N, N-dimethylformamide solution respectively, and then mixing the two dissolved solutions at room temperature to obtain a mixed solution C; Step 9: adding methanol to the mixed solution C obtained in step 8 to form a blue precipitate to obtain a mixture D, and the obtained mixture D is sealed at room temperature for 24 hours; Step 10: Filter the mixture D obtained in step 9 to obtain a blue powder, wash the blue powder with N, N-dimethylformamide solution 3 times and methanol 3 times, and vacuum dry overnight to obtain MOP-(Cu); Step 11: dissolving cellulose in 1-allyl-3-methylimidazolium chloride, heating and stirring, adding N, N-dimethylformamide as a co-solvent to obtain a yellow transparent cellulose solution, adding 2-bromoisobutyryl bromide dropwise to the cellulose solution, and stirring thoroughly to obtain a mixture E; Step 12: pouring the mixture E obtained in step 11 into deionized water to obtain cellulose-Br, and vacuum drying the obtained cellulose-Br; Step 13: dissolving the cellulose-Br obtained in step 12 in dimethyl sulfoxide to obtain a clear solution, and dissolving methyl 3-mercaptopropionate and triethylamine in dimethyl sulfoxide at the same time, and after stirring, adding carbon disulfide to the cellulose-Br solution, and continuously stirring at room temperature overnight; Step 14: precipitating the product obtained in step 13 in deionized water, filtering, washing with ethanol, and vacuum drying to obtain cellulose-CTA; Step 15: Add cellulose-CTA, butyl acrylate, 1-vinylimidazole and N, N-dimethylformamide to a stirred container; Step 16: degas the solution in the stirring container in step 15 by freeze-pump-thaw cycle and then seal it, immerse the stirring container in an oil bath, and after sufficient polymerization reaction, pour the mixture obtained in the stirring container into a mixed solution of water and N, N-dimethylformamide for precipitation, and vacuum dry the precipitated product; Step 17: dissolving the MOP-(Cu) powder in dichloromethane, dissolving the product obtained in step 16 in N, N-dimethylformamide, and mixing the two solutions obtained at room temperature; Step 18: Add bis(trifluoromethane)sulfonyl imide lithium salt powder to the mixed solution obtained in step 17, stir to obtain mixture F, transfer mixture F to a polytetrafluoroethylene culture dish, evaporate the solvent of mixture F under ambient conditions to form a defect-free polymer film, and then dry the polymer film in vacuum to completely remove the solvent, thereby obtaining the metal organic polyhedron-based polymer electrolyte.

[0007] Preferably, in step 5, the volume ratio of tetrahydrofuran to methanol in mixture A is 1:1.

[0008] Preferably, in step 7, the concentration of the hydrochloric acid solution is 0.5-2 mol / L.

[0009] Preferably, in step 8, the weight ratio of the ligand to cupric acetate is 1:1.

[0010] Preferably, in step 16, the polymerization time is 3-6 h.

[0011] The metal organic polyhedron based polymer electrolyte prepared by the above-mentioned preparation method is a metal organic polyhedron based polymer electrolyte.

[0012] The above-mentioned metal organic polyhedron-based polymer electrolyte is used in the preparation of solid-state lithium batteries.

[0013] The beneficial effects of the present invention are: 1. The metal-organic polyhedron-based coordination cross-linked polymer solid electrolyte provided by the present invention takes the unsaturated metal active sites of the metal-organic polyhedron as the coordination center, and coordinates and cross-links them with a cellulose-based polymer to prepare a super-cross-linked metal-organic polyhedron coordination polymer solid electrolyte. At the same time, the new coordination-driven cross-linked polymer electrolyte provided by the present invention does not contain any liquid and belongs to a fully solid-state electrolyte. It has a significant inhibitory effect on lithium dendrites during battery operation, can avoid battery short-circuit failure, and significantly improve the cycle life of solid-state lithium batteries.

[0014] 2. The metal organic polyhedron-based coordinated cross-linked polymer solid electrolyte provided by the present invention is different from the transmission mode between the traditional linear polymer electrolyte chain segments. It provides a three-dimensional connected lithium ion transmission path, which can effectively reduce the energy barrier of lithium ion transmission and achieve a lower activation energy, achieving 1.02×10 −3 S cm −1 The high lithium ion conductivity effectively solves the problem of low room temperature ion conductivity of existing polymer electrolytes.

[0015] 3. The metal-organic polyhedron-based coordination cross-linked polymer solid electrolyte provided by the present invention can provide a higher oxidation potential and will not cause overcharging when matched with a high-voltage positive electrode material.

[0016] 4. The super-crosslinked node metal-organic polyhedron-based coordination cross-linked polymer solid electrolyte provided by the present invention is conducive to the formation of a processable membrane material with excellent mechanical and dynamic properties.

[0017] 5. The metal-organic polyhedron-based coordinated cross-linked polymer solid electrolyte provided by the present invention can be adjusted and customized according to the type and functional group of the metal-organic polyhedron or macromolecule. Therefore, this new generation of functional soft materials based on metal-organic polyhedrons are easy to process, reuse, customize and integrate functions according to application scenarios, and are expected to expand the application field of metal-organic polyhedrons and provide new solutions for the construction of multifunctional materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is an optical picture of the CHMOP-Li solid electrolyte membrane prepared in Example 1 of the present invention; Figure 2 The impedance curve of the CHMOP-Li solid electrolyte membrane prepared in Example 1 of the present invention at room temperature; Figure 3 This is an optical photograph of the CHMOP-Li solid electrolyte membrane prepared in Example 1 of the present invention in a bending test; Figure 4 The cycle performance curve of the solid-state lithium metal battery prepared in Example 2 of the present invention; Figure 5 This is an optical picture of the solid electrolyte membrane prepared in Comparative Example 1 of the present invention; Figure 6 The impedance curve of the solid electrolyte membrane prepared in Comparative Example 1 of the present invention at room temperature; Figure 7 This is the cycle performance curve of the solid-state lithium metal battery prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0020] Example 1: 5-hydroxydimethyl isophthalate (18 mmol) and potassium carbonate (45 mmol) were dissolved in an acetone solution (120 mL) and stirred at 70°C for 1 h, and then 1-bromobutane (19.6 mmol) was added to 60 mL of the acetone solution, stirred thoroughly, and added to the above reaction solution to react for 6 h. After the reaction was completed, the above reaction solvent was evaporated and the residue was mixed with ultrapure water, and then extracted with dichloromethane. The combined organic phase was dried over sodium sulfate and evaporated to obtain a white solid, which was recrystallized from methanol to obtain the product 5-butoxydimethyl isophthalate; 5-Butoxydimethylisophthalate (11.7 mmol) was dissolved in 200 mL of a mixture of tetrahydrofuran / methanol (1:1), and a certain concentration of sodium hydroxide solution was added to the mixture. The reaction mixture was stirred under reflux for 24 h. Once cooled to room temperature, the organic solvent was removed under vacuum. Subsequently, a certain concentration of hydrochloric acid solution was added to the aqueous residue until the pH of the solution reached 5 to obtain a white solid. The mixture was then centrifuged and the supernatant was removed. The precipitate was washed with water and dried under vacuum to obtain the ligand of the metal organic polyhedron. The ligand and copper acetate (1:1) were dissolved in 100 mL and 50 mL N, N-dimethylformamide solution, respectively. The two solutions were then mixed at room temperature. 100 mL of methanol was added to the mixed solution to form a blue precipitate immediately. The resulting mixture was sealed at room temperature for 24 hours. After filtration, a blue powder was obtained. The powder was washed with N, N-dimethylformamide solution for 3 times and methanol for 3 times, respectively. After vacuum drying at 80 °C overnight, MOP-(Cu) was obtained. 12.4 mmol of cellulose was dissolved in 1-allyl-3-methylimidazolium chloride (40 g), and N, N-dimethylformamide (20.0 mL) was added as a co-solvent after stirring at 80 °C for 2 h to obtain a yellow transparent cellulose solution. 2-Bromoisobutyryl bromide (14.2 g, 62.0 mmol) was added dropwise to the reaction solution in an ice / water bath. After the addition was completed, the reaction mixture was stirred at ambient temperature for 24 h. After the reaction was completed, the reaction mixture was poured into excess deionized water to obtain a white flocculent precipitate (cellulose-Br), which was dried under vacuum at 50 °C for 12 h. The dried cellulose-Br (0.9 g, 3 mmol Br) was dissolved in dimethyl sulfoxide (24 mL) to obtain a clear solution. At the same time, methyl 3-mercaptopropionate (113.2 μL, 1.0 mmol, 0.31 eq.) and triethylamine (142.4 μL, 1.0 mmol, 0.31 eq.) were dissolved in dimethyl sulfoxide (5.8 mL). After stirring for 10 min, carbon disulfide (166.1 μL, 2.8 mmol, 0.84 eq.) was added to the cellulose-Br solution, and the reaction mixture was continuously stirred at room temperature overnight. The product was then precipitated in excess deionized water, filtered, washed with ethanol, and dried in vacuo at 70 °C to obtain a light yellow solid (cellulose-CTA); The obtained cellulose-CTA (120 mg, 0.12 mmol CTA), butyl acrylate (15.4 g, 120 mmol), 1-vinylimidazole (1.9 g, 20 mmol) and N, N-dimethylformamide (30 mL) were added to a flask equipped with a magnetic stirring bar, and the solution was degassed by freeze-pump-thaw cycles and then sealed. The sealed tube was further immersed in an oil bath at 70°C. After a certain polymerization time, the reaction was stopped, and the obtained mixture was precipitated in a large amount of water-N, N-dimethylformamide mixture (4:1, v / v). The obtained product was further dried at 60°C under vacuum for 24 h to obtain a dry product; MOP-(Cu) powder (50 mmol) was dissolved in dichloromethane, and the resulting dry product (300 mg) was dissolved in N,N-dimethylformamide, and the two solutions were mixed at room temperature. Lithium bis(trifluoromethane)sulfonyl imide powder (100 mmol) was added to the above mixture. After stirring for 10 min, the mixture was transferred to a polytetrafluoroethylene dish (10 cm in diameter) and the solvent was allowed to evaporate in a fume hood under ambient conditions to form a defect-free polymer film. The film was then dried in a vacuum oven at 80 °C to completely remove the solvent. The dry film was cut into the required size for further testing and battery assembly.

[0021] The CHMOP-Li solid electrolyte membrane prepared in Example 1 of the present invention was characterized.

[0022] See also Figure 1 , Figure 1 This is an optical picture of the CHMOP-Li solid electrolyte membrane prepared in Example 1.

[0023] Depend on Figure 1 It can be seen that the CHMOP-Li solid electrolyte membrane prepared in the present invention is uniform and dense, and has excellent mechanical strength.

[0024] The performance of the CHMOP-Li solid electrolyte membrane prepared in Example 1 of the present invention was tested.

[0025] The CHMOP-Li solid electrolyte membrane was punched into a disc with a diameter of 16 mm and placed between two stainless steel discs for ionic conductivity testing.

[0026] See also Figure 2 , Figure 2 This is the impedance curve of the CHMOP-Li solid electrolyte membrane prepared in Example 1 at room temperature.

[0027] Depend on Figure 2 The curve shows that the ionic conductivity of CHMOP-Li solid electrolyte membrane is 1.02×10 −3 S cm −1 .

[0028] The mechanical properties of the CHMOP-Li solid electrolyte membrane prepared in Example 1 of the present invention were tested.

[0029] See also Figure 3 , Figure 3 This is an optical photograph of the CHMOP-Li solid electrolyte membrane prepared in Example 1 in a bending test.

[0030] Depend on Figure 3 It can be seen that the CHMOP-Li solid electrolyte membrane prepared in the present invention can restore its original shape after the bending test.

[0031] Example 2: CHMOP-Li is assembled into a solid-state lithium metal battery, which includes a metal lithium negative electrode, a CHMOP-Li solid electrolyte membrane, and an NCM-523 solid positive electrode material.

[0032] The solid-state lithium metal battery prepared in Example 2 of the present invention was subjected to a charge and discharge performance test under the following test conditions: room temperature, current density of 0.2 C, and cut-off voltage of 2.2-4.35 V.

[0033] See also Figure 4 , Figure 4 The cycle performance of the solid-state lithium metal battery prepared in Example 2.

[0034] Depend on Figure 4 It can be seen that the number of cycles of Example 2 at a current density of 0.2 C can reach 300.

[0035] Comparative Example 1: 12.4 mmol of cellulose was dissolved in 1-allyl-3-methylimidazolium chloride (40 g), and N, N-dimethylformamide (20.0 mL) was added as a co-solvent after stirring at 80 °C for 2 h to obtain a yellow transparent cellulose solution, and 2-bromoisobutyryl bromide (14.2 g, 62.0 mmol) was added dropwise to the reaction solution in an ice / water bath. After the addition was completed, the reaction mixture was stirred at ambient temperature for 24 h. After the reaction was completed, the reaction mixture was poured into excess deionized water to obtain a white flocculent precipitate (cellulose-Br), which was dried under vacuum at 50 °C for 12 h; The dried cellulose-Br (0.9 g, 3 mmol Br) was dissolved in dimethyl sulfoxide (24 mL) to obtain a clear solution. At the same time, methyl 3-mercaptopropionate (113.2 μL, 1.0 mmol, 0.31 eq.) and triethylamine (142.4 μL, 1.0 mmol, 0.31 eq.) were dissolved in dimethyl sulfoxide (5.8 mL). After stirring for 10 min, carbon disulfide (166.1 μL, 2.8 mmol, 0.84 eq.) was added to the cellulose-Br solution, and the reaction mixture was continuously stirred at room temperature overnight. The product was then precipitated in excess deionized water, filtered, washed with ethanol, and dried in vacuo at 70 °C to obtain a light yellow solid (cellulose-CTA); The obtained cellulose-CTA (120 mg, 0.12 mmol CTA), butyl acrylate (15.4 g, 120 mmol), 1-vinylimidazole (1.9 g, 20 mmol) and N, N-dimethylformamide (30 mL) were added to a flask equipped with a magnetic stirring bar, and the solution was degassed by freeze-pump-thaw cycles and then sealed. The sealed tube was further immersed in an oil bath at 70 °C. After a certain polymerization time, the reaction was stopped, and the obtained mixture was precipitated in a large amount of water-N, N-dimethylformamide mixture (4:1, v / v). The obtained product was further dried at 60 °C under vacuum for 24 h to obtain a dry product; The dried product (300 mg) was dissolved in N, N-dimethylformamide, and 100 mmol of bis(trifluoromethane)sulfonyl imide lithium salt powder was added to the above mixture. After stirring for 10 min, the mixture was transferred to a polytetrafluoroethylene petri dish (10 cm in diameter); The solvent was allowed to evaporate under ambient conditions in a fume hood to form a defect-free polymer film, and then the film was dried in a vacuum oven at 80° C. to completely remove the solvent. The dried film was cut into desired sizes for further testing and battery assembly.

[0036] The solid electrolyte membrane prepared in Comparative Example 1 of the present invention was characterized.

[0037] See also Figure 5 , Figure 5 This is an optical picture of the solid electrolyte membrane prepared in Comparative Example 1.

[0038] Depend on Figure 5 It can be seen that the solid electrolyte membrane prepared by the present invention has film-forming ability and has a certain strength.

[0039] The performance of the solid electrolyte membrane prepared in Comparative Example 1 of the present invention was tested.

[0040] The solid electrolyte membrane was punched into a disc with a diameter of 16 mm and placed between two stainless steel discs for ionic conductivity testing.

[0041] See also Figure 6 , Figure 6 This is the impedance curve of the solid electrolyte membrane prepared in Comparative Example 1 at room temperature.

[0042] Depend on Figure 6 The curve can be calculated that the ionic conductivity of the solid electrolyte membrane is 2.5×10 −5 S cm −1 .

[0043] Comparative Example 2 Assembling solid-state lithium metal batteries with solid electrolyte membranes: The battery includes a metallic lithium negative electrode, a solid electrolyte membrane, and an NCM-523 solid positive electrode material.

[0044] The solid-state lithium metal battery prepared in Comparative Example 2 of the present invention was subjected to a charge and discharge performance test, and the test conditions were: room temperature, a current density of 0.2 C, and a cut-off voltage of 2.2-4.35 V.

[0045] See also Figure 7 , Figure 7 The cycle performance of the solid-state lithium metal battery prepared in Comparative Example 2.

[0046] Depend on Figure 7 It can be seen that the number of cycles of Comparative Example 2 at a current density of 0.2 C is only 36.

[0047] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a metal organic polyhedron based polymer electrolyte, characterized in that: The following steps are involved: Step 1: Dissolve dimethyl 5-hydroxyisophthalate and potassium carbonate in acetone solution and stir thoroughly; Step 2: Add 1-bromobutane to the acetone solution, stir thoroughly, and then add to the reaction solution obtained in step 1 to react thoroughly; Step 3: evaporating the reaction solvent in the solution obtained in step 2, and mixing the residue with ultrapure water, followed by extraction with dichloromethane to obtain a combined organic phase; Step 4: Dry the combined organic phase obtained in step 3 with sodium sulfate and evaporate to obtain a white solid, and recrystallize the obtained white solid from methanol to obtain the product 5-butoxydimethylisophthalate; Step 5: dissolving dimethyl 5-butoxyisophthalate in a mixture A of tetrahydrofuran and methanol, and adding a sodium hydroxide solution to the mixture A to obtain a reaction mixture; Step 6: stirring the reaction mixture obtained in step 5 under reflux, cooling to room temperature, and removing the organic solvent under vacuum to obtain a water-containing residue; Step 7: adding a hydrochloric acid solution to the aqueous residue obtained in step 6 until the pH of the solution reaches 5 to obtain a mixture B containing a white solid, then centrifuging the mixture B and removing the supernatant to obtain a precipitate, washing the precipitate with water and vacuum drying to obtain a ligand of a metal organic polyhedron; Step 8: Dissolving the obtained metal organic polyhedron ligand and copper acetate in N, N-dimethylformamide solution respectively, and then mixing the two dissolved solutions at room temperature to obtain a mixed solution C; Step 9: adding methanol to the mixed solution C obtained in step 8 to form a blue precipitate to obtain a mixture D, and the obtained mixture D is sealed at room temperature for 24 hours; Step 10: Filter the mixture D obtained in step 9 to obtain a blue powder, wash the blue powder with N, N-dimethylformamide solution 3 times and methanol 3 times, and vacuum dry overnight to obtain MOP-(Cu); Step 11: dissolving cellulose in 1-allyl-3-methylimidazolium chloride, heating and stirring, adding N, N-dimethylformamide as a co-solvent to obtain a yellow transparent cellulose solution, adding 2-bromoisobutyryl bromide dropwise to the cellulose solution, and stirring thoroughly to obtain a mixture E; Step 12: pouring the mixture E obtained in step 11 into deionized water to obtain cellulose-Br, and vacuum drying the obtained cellulose-Br; Step 13: dissolving the cellulose-Br obtained in step 12 in dimethyl sulfoxide to obtain a clear solution, and dissolving methyl 3-mercaptopropionate and triethylamine in dimethyl sulfoxide at the same time, and after stirring, adding carbon disulfide to the cellulose-Br solution, and continuously stirring at room temperature overnight; Step 14: precipitating the product obtained in step 13 in deionized water, filtering, washing with ethanol, and vacuum drying to obtain cellulose-CTA; Step 15: Add cellulose-CTA, butyl acrylate, 1-vinylimidazole and N, N-dimethylformamide to a stirred container; Step 16: degas the solution in the stirring container in step 15 by freeze-pump-thaw cycle and then seal it, immerse the stirring container in an oil bath, and after sufficient polymerization reaction, pour the mixture obtained in the stirring container into a mixed solution of water and N, N-dimethylformamide for precipitation, and vacuum dry the precipitated product; Step 17: dissolving the MOP-(Cu) powder in dichloromethane, dissolving the product obtained in step 16 in N, N-dimethylformamide, and mixing the two solutions obtained at room temperature; Step 18: Add bis(trifluoromethane)sulfonyl imide lithium salt powder to the mixed solution obtained in step 17, stir to obtain mixture F, transfer mixture F to a polytetrafluoroethylene culture dish, evaporate the solvent of mixture F under ambient conditions to form a defect-free polymer film, and then dry the polymer film in vacuum to completely remove the solvent, thereby obtaining the metal organic polyhedron-based polymer electrolyte.

2. The method for preparing a metal organic polyhedron based polymer electrolyte according to claim 1, characterized in that: In step 5, the volume ratio of tetrahydrofuran to methanol in mixture A is 1:

1.

3. The method for preparing a metal organic polyhedron based polymer electrolyte according to claim 1, characterized in that: In step 7, the concentration of the hydrochloric acid solution is 0.5-2 mol / L.

4. The method for preparing a metal organic polyhedron based polymer electrolyte according to claim 1, characterized in that: In step 8, the weight ratio of the ligand to copper acetate is 1:

1.

5. The method for preparing a metal organic polyhedron based polymer electrolyte according to claim 1, characterized in that: In step 16, the polymerization time is 3-6 h.

6. A metal-organic polyhedron-based polymer electrolyte prepared by the method for preparing a metal-organic polyhedron-based polymer electrolyte as claimed in any one of claims 1 to 5.

7. Use of a metal organic polyhedron-based polymer electrolyte as claimed in claim 6 in the preparation of a solid-state lithium battery.